Analogy and Comparative Study of Hydroxypropyl Methylcellulose (HPMC) Biopolymer with Graphene Oxide and Zinc Oxide Nano Fillers - Padinhattayil, Sanoop; Sheshappa Rai, K. (Asian Journal of Chemistry, 2021)
Present study describes the analogy and comparative study of polymer nanocomposites with the known polymer matrix hydroxypropyl methylcellulose (HPMC) incorporated with graphene oxide (GO) and zinc oxide (ZnO) nanoparticles as nano fillers. The polymer nanocomposite films were carried out using solution casting method and characterized by IR spectroscopy, XRD analysis, mechanical properties, thermal characterization and optical microscopy analysis. There were several changes in the HPMC polymer by the addition of nanoparticles of GO and ZnO in structural, thermal, mechanical and optical properties. The thermal stability of the composite films increased as compared with the pure HPMC whereas the mechanical study shows a variation of down values.